2015
DOI: 10.3390/ijms161023390
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Induced Antibiotic Resistance in Bacterium LSJC7

Abstract: Co-contamination of antibiotics and heavy metals prevails in the environment, and may play an important role in disseminating bacterial antibiotic resistance, but the selective effects of heavy metals on bacterial antibiotic resistance is largely unclear. To investigate this, the effects of heavy metals on antibiotic resistance were studied in a genome-sequenced bacterium, LSJC7. The results showed that the presence of arsenate, copper, and zinc were implicated in fortifying the resistance of LSJC7 towards tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 51 publications
8
79
2
1
Order By: Relevance
“…Determination of some heavy metals. Of the whole list of chemical elements measured following the hypothesis of the current study, only four chemical elements were reported as being heavy metals notably Cu, Cd, Zn and Hg of environmental importance as involved in the resistance of microorganisms as previously described [39].…”
Section: The Micro-dilution Test In a Liquid Environmentmentioning
confidence: 59%
See 3 more Smart Citations
“…Determination of some heavy metals. Of the whole list of chemical elements measured following the hypothesis of the current study, only four chemical elements were reported as being heavy metals notably Cu, Cd, Zn and Hg of environmental importance as involved in the resistance of microorganisms as previously described [39].…”
Section: The Micro-dilution Test In a Liquid Environmentmentioning
confidence: 59%
“…One possible explanation of such improvement of antibiotic resistance is that the presence of heavy metals enhanced the enrichment and growth of indigenous bacteria in the microbial community, which are already bearing antibiotic resistance genes; another possibility is that the resistance in bacteria which is sensitive to antibiotics could be induced due to the co-existence of heavy metals and antibiotics in the environment. Some investigations have demonstrated the positive correlation between the abundance of antibiotic resistance genes and the elevated concentrations of antibiotic and heavy metals in environments [39]. We have to note that the environment acts both as a reservoir of resistance traits and a bioreactor containing chemical stressors and opportunities for genetic exchange.…”
Section: Elements/concentrations Samples Aluminium Silicium Phosphorumentioning
confidence: 98%
See 2 more Smart Citations
“…Although our study is based on P 1B -type-ATPases that confer resistance to metals, the analysis of multiplicity and diversity of transporters have general implications for the evolution of resistance, adaptation and innovation in bacteria. For instance, the co-existence of antibiotics and metals in the environment has conducted to the co-evolution of their mechanisms of resistance; the antibiotic resistance induced by exposure to toxic metals is well documented (Berg, Tom-Petersen, & Nybroe, 2005;Chen et al, 2015;Stepanauskas et al, 2006). Furthermore, metals and antibiotic resistance genes tend to cooccurr (Pal, Bengtsson-Palme, Kristiansson, & Larsson, 2015;Su, Ye, & Zhu, 2012).…”
Section: What Is the Function Of Multiple And Diverse Cu-atpases?mentioning
confidence: 99%